The Use of Generative AI in Investment and Budgeting Decision-Making Among Business Students: A Qualitative Analysis of Public Digital Artifacts - Aldo Franco Karinda; Harke Revo Leonard Polii; Rifal Richard Pangemanan (STIE Amkop Makassar, 2026)
This study analyzes how public digital artifacts relevant to the context of business students frame the use of generative AI in investment and budgeting decisions, how trust and risk perceptions toward AI outputs are represented, and how norms of use are displayed in the digital ecology. The study uses a qualitative approach through a thematic-interpretive analysis of public digital artifacts from TikTok, X, Threads, YouTube, and Stockbit during January 2025–February 2026. The final analytical corpus consists of 44 selected public entries, which include 39 cross-platform primary digital artifacts and 5 contextually reinforcing sources of limited use. The discussion of the themes relies primarily on primary artifacts on YouTube, X, and Stockbit, while TikTok and Threads are used primarily to clarify the digital norm ecology. The analysis yields four main patterns: AI is interpreted as a financial co-pilot ; trust in AI is selective and contextual; verification and affirmation of human judgment become norms of use; and digital spaces play a role in both normalizing and limiting the use of AI. These findings suggest that financial behavior in the context of business students in the AI era is more appropriately understood as a digital representation shaped by the interaction between economic rationality, calibration of trust in technology, and digital communication culture